Penerapan Algoritma Boyer Moore Dalam Pencarian Barang Hilang pada Aplikasi FindIt Berbasis Android - Setiawan, Muhammad Afif; Andryana, Septi; Gunaryati, Aris (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Losing is an experience that every human has experienced during his life span, and this is a natural thing. Loss of goods is an event that can make a person panic, especially if the lost item is valuable to him. Therefore, with the development of technology, the author tries to design an application that can be a medium for information on lost items for the community, this application is designed based on Android and is named FindIt. This FindIt app uses Firebase Authentication and Firebase Storage as the main database. This application can be run in real-time because it uses Realtime Firebase. Algorithm testing was carried out between Knuth Morris Pratt and Boyer Moore, and the result is Boyer Moore is faster in string matching. The test results using this algorithm are 100% accurate. Application testing is done using the Blackbox method, where the functions and features of the application run as expected. With this application, it is hoped that the community can help each other to find goods and post their findings on this application